Analysis of Factors Influence Pandu Gym Business Development in Kuningan Regency - Suwarno, Henky Lisan; Thendjaya, Leonard (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Problems occurrings in the Gym business in Kuningan Regency are related to the quality of the Gym, starting from inadequate the Gym machines, services that do not meet consumer needs, lack of collaboration partner strategies with supplement brands etc. The purpose of this research is to find out what factors influence the development of Gym business in Kuningan district. The type of the research which used by writer is Qualitative method and The data collection method that used by writer is data triangulation method and triangulation method, writer did Interview, observation, and case studies towards informants who live in Kuningan Regency, This research’s informant is Niko Senjaya as the owner of Pandu Gym, consumer, Practitioner/Personal Trainer, and Academics/Business Consultans. The Research’s result showed that Partners and Collaborations, ongoing Trends on Social media, Consumer’s Needs and Satisfactions, have a positive and significant influence towards external factors which influence Gym business development. Gym’s machine quality, HR quality development and innovation, Discounts and Services, Direct and Digital Marketing Strategy, Financial and Operational Management, have a positive and significant influence towards internal factors which influence The Gym Business development. This Research has Implications for Gym Businessmen to develop The Gym Business in Kuningan Regency by focusing onto Factors which influence Service Development and others as Promotional Strategies.